On the road with Siri Sande: excavating Petropigi Castle, a Late Byzantine statio on the via Egnatia in Eastern Macedonia - Øystein Ekroll (Acta ad Archaeologiam et Artium Historiam Pertinentia)
The castle of Petropigi is a small, ruined castle near the village of Petropigi, 20 km east of the town of Kavala in the province of Eastern Macedonia in northern Greece. It is situated on the narrow coastal plain between the delta of the river Nestos and the foothills of the Rhodopi Mountains, close to the modern road, which was only recently replaced by the new EU-funded Via Egnatia, which is carved into the hills behind the village. The excavation (1993-1999) was conducted by a team of Norwegian archaeologists led by Professor Siri Sande. The project was initiated by The Norwegian Institute of Athens in cooperation with the Ephorate of Byzantine Antiquities of Eastern Macedonia in Kavala, led by Dr Charalambos Bakirtzis. The castle of Petropigi had a function that was very unusual in Western Europe, as it was built by the Byzantine state to protect a stretch of an important communication route between Constantinople and Thessaloniki, the two largest cities of the Byzantine Empire.